The XMM Cluster Survey: Present status and latest results. Issue 4 (2nd May 2013) - Viana, P.T.P.; Mehrtens, N.; Harrison, C.D.; Romer, A.K.; Collins, C.A.; Hilton, M.; Hoyle, B.; Kay, S.T.; Liddle, A.R.; Mayers, J.A.; Miller, C.J.; Rooney, P.J.; et al.
Abstract The XMM Cluster Survey (XCS) is a serendipitous search for galaxy clusters using all publicly available data in the XMM‐Newton Science Archive. Our recent first data release (XCS‐DR1) contains 503 optically confirmed groups and clusters, among which 256 new to the literature and 357 whose X‐ray emission was detected for the first time. We discuss their properties and provide an update on the work being done. As examples of the applications of XCS‐DR1, we mention the 17 fossil groups/clusters identified with the help of the Sloan Digital Sky Survey. Their brightest galaxies have stellar populations and star‐formation histories which are similar to normal brightest cluster galaxies, but their stellar masses are significantly larger and correspond to a much bigger fraction of the total group/cluster optical luminosity. We also highlight the 15 clusters expected tobe also detected by the Planck satellite, and characterize the expected overlap between the final XCS and Planck cluster catalogues. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)